2014
DOI: 10.1111/1755-5922.12084
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with Severe PH due to Lung Disease with and without Targeted Therapy

Abstract: SUMMARYIntroduction: Pulmonary hypertension (PH) can occur in patients with lung disease and worsen prognosis. Endothelin receptor antagonists, phosphodiesterase 5-inhibitors, and prostacyclin analogs, referred to as targeted therapy, have not been shown in a limited number of controlled clinical studies to improve exercise capacity in these patients. Possibly targeted therapy could be of benefit in patients with severe PH due to lung disease, but this subgroup is not well studied. Aims: To analyze influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
0
19
0
1
Order By: Relevance
“…Studies of ET receptor antagonists have specifically targeted fibrosis rather than the complicating PH. Although a few studies have shown that targeted therapy with PDE-5 inhibitors or prostacyclin analogues can improve exercise capacity [46], the use of targeted therapy in patients with PH in the context of significant lung disease is not supported by evidence derived from randomised controlled trials, and there is no agent with regulatory approval for this indication.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ET receptor antagonists have specifically targeted fibrosis rather than the complicating PH. Although a few studies have shown that targeted therapy with PDE-5 inhibitors or prostacyclin analogues can improve exercise capacity [46], the use of targeted therapy in patients with PH in the context of significant lung disease is not supported by evidence derived from randomised controlled trials, and there is no agent with regulatory approval for this indication.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies reached contradictive results. Lange et al recently described a better survival in a retrospective cohort of treated PH-COPD, but no effect of therapy on the exercise capacity [19]. Blanco et al investigated the effect of sildenafil given for 3 months in addition to training to COPD patients with mild PH at echocardiography [20].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension is commonly associated with chronic lung disease, but severe PH is rare, defined as mPAP of ≥35 mmHg. Lange et al did show a survival benefit with vasodilators in patients with severe PH in lung disease, but not in the mild/moderate groups 46 . It has been shown that although pulmonary vasodilators do reduce NTproBNP in severe Group 3 PH, there was no significant increase in 6-minute walk distance.…”
Section: Management Of Group 3 Phmentioning
confidence: 93%